2012
DOI: 10.4103/0300-1652.103549
|View full text |Cite
|
Sign up to set email alerts
|

How are our medical students using the computer and internet? A study from a medical college of north India

Abstract: Background:In today's world, use of Internet has become indispensable. Medical students have much to gain from the Internet technology that has revolutionized the medical field. There is a very rapid change in the way communication technology is being handled and our medical students should also be ready to embrace it. Very few studies have been done on this topic in India. The aim was to find out the knowledge, practice, and barriers of Internet use among the medical undergraduates of Subharti Medical College… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 8 publications
0
26
2
2
Order By: Relevance
“…This is in contrast with another Indian study by Maroof et al 11 in which it was found that 53.7% of the medical students accessed the internet using a personal computer. In the same study, it was also found that the majority (58.5%) were using it for communication and entertainment, and only about a third were using it to access medical information (27.7% for medical literature and 32.4% for accessing content related to medical procedures, videos and pictures).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This is in contrast with another Indian study by Maroof et al 11 in which it was found that 53.7% of the medical students accessed the internet using a personal computer. In the same study, it was also found that the majority (58.5%) were using it for communication and entertainment, and only about a third were using it to access medical information (27.7% for medical literature and 32.4% for accessing content related to medical procedures, videos and pictures).…”
Section: Discussioncontrasting
confidence: 82%
“…In the study of Maroof et al 11 it was also found that the proportion of year III medical students using the internet was higher than first year medical students, and male students were using it for longer than female students. However, in our study, although more male students accessed the internet for longer than female students, the proportion of IX semester students accessing the internet for a longer time was smaller than VIII semester students.…”
Section: Discussionmentioning
confidence: 97%
“…Ranasinghe et al, [9] stated that the students used computers predominately for; word processing (95.6%), entertainment (95.0%), web browsing (80.1%) and preparing presentations (76.8%). In a study which was conducted in Meerut, India, Maroof KA and co-workers [10] showed that the main use of the Internet was for communication (58.5%) and entertainment (46.3%) and that only about one-fifths of the respondents used the Internet for searching literature for projects from the medical journals which are there on the Internet. Jadoon et al, [11] stated that 61.0% used the internet for both academic and Personal activities, while 17% used it for academic activities [Table /Fig-3].…”
Section: Resultsmentioning
confidence: 99%
“…Even developing countries are taking efforts to acknowledge the technological expansions. Health professional students now have a strong base to utilize information technology for their professional development [6].…”
Section: Introductionmentioning
confidence: 99%